THE EFFECT OF BIOJUK TREATMENT ON DECREASING TOM AND BOD LEVELS CONTAINED ON RIVER SAIL WATER IN PEKANBARU CITY - Hawari Putriningsih; Budijono Budijono; M. Hasbi M. Hasbi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTSail River is one of the rivers in the city of Pekanbaru that has been polluted with organic pollutants. This study aims to determine the decrease in TOM and BOD levels by using different bioijuk densities. This research was carried out on the Sail River, in March-April 2019. The method used was an incomplete design (CRD), with 3 treatments of bioijuk density namely P1 (low density), P2 (medium density) and P3 (high density), and each -one with 3 replications. The sampling location was selected in the inlet section (before passing bioijuk) and the outlet section (after passing bioijuk) artificial ditch. The results showed that the highest decrease in TOM levels occurred in P2 (0.046 mg / L) with a decrease in effectiveness (EP) of 95%. The highest decrease in BOD levels was found in P2 (4.66 mg / L) with an EP of 53%. It turns out that the treatment of different bioijuk densities does not have a significant effect on decreasing levels of the TOM and BOD of the Sail River.Keywords: Bioijuk, TOM, BOD, bacteria, effective sperm